2014
DOI: 10.1016/j.jpeds.2014.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Skeletal Survey by Age in Children Referred to Abuse Specialists

Abstract: Among 2609 subjects, 2036 (78%) had skeletal survey and 458 (18%) had at least one new fracture identified. For all age groups up to 36 months, skeletal survey was obtained in >50% of subjects, but rates decreased to less than 35% for subjects >36 months. New fracture identification rates for skeletal survey were similar between children 24-36 months of age (10.3%, 95% CI 7.2-14.2) and children 12-24 months of age (12.0%, 95% CI 9.2-15.3) CONCLUSIONS: Skeletal surveys identify new fractures in an important fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 38 publications
1
39
2
Order By: Relevance
“…They also mention that there were no other fractures detected or any other significant injuries to support a diagnosis of nonaccidental injury. Most children diagnosed with non-accidental injury do not have other fractures or significant injuries [4]. Therefore, to postulate the idea that infants with limited mobility can fracture a long bone in the absence of the intervention of an external party without analyzing all factors that affect bone fractures is, to my belief, incorrect.…”
mentioning
confidence: 98%
“…They also mention that there were no other fractures detected or any other significant injuries to support a diagnosis of nonaccidental injury. Most children diagnosed with non-accidental injury do not have other fractures or significant injuries [4]. Therefore, to postulate the idea that infants with limited mobility can fracture a long bone in the absence of the intervention of an external party without analyzing all factors that affect bone fractures is, to my belief, incorrect.…”
mentioning
confidence: 98%
“…Infant ICH that occurred indoors or for which the injury scene is unknown are justifiably regarded as possible instances of child abuse . But of the 37 such patients surveyed, a considerable percentage did not undergo skeletal surveys or funduscopy (38% and 41%, respectively), which are critical screening tests for abuse in children . One partial explanation may be that frontline medical personnel lack sufficient awareness of medical treatment for child abuse; the absence of trauma evaluation and care protocol developed from the viewpoint of child abuse may be another …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] But of the 37 such patients surveyed, a considerable percentage did not undergo skeletal surveys or funduscopy (38% and 41%, respectively), which are critical screening tests for abuse in children. [17][18][19][20][21][22][23] One partial explanation may be that frontline medical personnel lack sufficient awareness of medical treatment for child abuse; 6,9,24,25 the absence of trauma evaluation and care protocol developed from the viewpoint of child abuse may be another. 26 A significant number of child abuse cases may not have been reported to hospital-based CPT or regional CPS in Yokohama.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Trauma Registry database records, we identified all pediatric patients (≤ 3 years old) who underwent a skeletal survey during this period. This age cutoff was based on the utility of skeletal surveys in the pediatric population demonstrated in previous clinical studies [20]. A medical chart review collected data on patient's demographic characteristics, 51A (initiation of a formal investigation for abuse or neglect in Massachusetts) status, skeletal survey results, additional imaging results, specific injuries, injury severity score, and patient's hospital course, mortality, and disposition (e.g., home, into custody).Confirmed NAT was defined as patients who satisfied all of the following criteria: 51-A filed, injuries inconsistent with history or mechanism of injury and child was removed from parental custody/ legal guardianship as per our institutional child protective program.…”
Section: Patient Populationmentioning
confidence: 99%
“…In fact, one study has suggested that children less than 6 months of age have more than two fold higher rates of a positive skeletal survey compared with children older than 6 months [11]. However, a more recent study demonstrated that skeletal surveys could have a similar diagnostic yield among patients as old as 36 months compared with younger children [20]. Inasmuch, further investigation into the role of the skeletal survey in identifying NAT in pediatric trauma patients is warranted.…”
Section: Introductionmentioning
confidence: 99%